Basic actions to reduce dropout rates in distance learning. (February 2018) - Gregori, Pablo; Martínez, Vicente; Moyano-Fernández, Julio José
Highlights: Online courses suffer from a large dropout rate of students, specially in Science and Engineering fields. Learning success depends highly on the level of engagement in the proposed activities which, in turn, demands a deeper involvement of staff. We analyze and propose several actions, which are necessary to get success to develop a distance scientific-technical training. Abstract: Today's society, which is strongly based on knowledge and interaction with information, has a key component in technological innovation, a fundamental tool for the development of the current teaching methodologies. Nowadays, there are a lot of online resources, such as MOOCs (Massive Open Online Courses) and distance learning courses. One aspect that is common to all of these is a high dropout rate: about 90% in MOOCs and 50% in the courses of the Spanish National Distance Education University, among other examples. In this paper, we analyze a number of actions undertaken in the Master's Degree in Computational Mathematics at Universitat Jaume I in Castellón, Spain. These actions seem to help decrease the dropout rate in distance learning; the available data confirm their effectiveness.